2017
DOI: 10.1371/journal.pone.0176566
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of facial morphology reveals novel associations with FREM1 and PARK2

Abstract: Several studies have now shown evidence of association between common genetic variants and quantitative facial traits in humans. The reported associations generally involve simple univariate measures and likely represent only a small fraction of the genetic loci influencing facial morphology. In this study, we applied factor analysis to a set of 276 facial linear distances derived from 3D facial surface images of 2187 unrelated individuals of European ancestry. We retained 23 facial factors, which we then test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 33 publications
4
75
0
Order By: Relevance
“…Interestingly, this study observed the same association between soft-tissue nasal width and PAX1 identified in Latin Americans (Adhikari et al, 2016). Lee et al identified two genetic variants of FREM1 and PARK2 associated with face shape in individuals of European ancestry (Lee et al, 2017). In 2018, two studies (Claes et al, 2018;Crouch et al, 2018) found a number of newly associated genetic loci by applying novel approaches to a European-derived cohort and replicated many loci in previous studies Paternoster et al, 2012;Adhikari et al, 2016;Shaffer et al, 2016).…”
Section: Introductionsupporting
confidence: 73%
“…Interestingly, this study observed the same association between soft-tissue nasal width and PAX1 identified in Latin Americans (Adhikari et al, 2016). Lee et al identified two genetic variants of FREM1 and PARK2 associated with face shape in individuals of European ancestry (Lee et al, 2017). In 2018, two studies (Claes et al, 2018;Crouch et al, 2018) found a number of newly associated genetic loci by applying novel approaches to a European-derived cohort and replicated many loci in previous studies Paternoster et al, 2012;Adhikari et al, 2016;Shaffer et al, 2016).…”
Section: Introductionsupporting
confidence: 73%
“…Additionally, in supplementary Note 2, Tables S3–S6 and Figures S4–S5, we first report statistical replication for 10 out of 16 SNPs from six previous facial GWAS based on 2D or 3D images 27 (Table S3). Second, we consulted GWAS central and Phenoscanner 29 and report additional evidence for nine SNPs in Table 1 (Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…In mice, whole-genome QTL studies have identified numerous genetic regions associated with craniofacial traits 3133 . In humans, both candidate gene 10,34,35 and GWAS 27 have implicated specific variants. While the highly complex nature of craniofacial morphogenesis suggests that many genes are likely to influence facial morphology, the number of associated loci uncovered so far using GWAS has been limited with few independent replications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there have been nine GWAS focused on quantifiable aspects of human craniofacial morphology. [15][16][17][18][19][20][21][22][23] The main characteristics and results of these studies are summarized in Table 1.…”
Section: Me a Suring Face S And Mapping G Ene Smentioning
confidence: 99%